REKONTEKSTUALISASI SYAIR DEMONSTRAN SUDAN DI MEDIA SOSIAL: ANALISIS WACANA KRITIS TERHADAP REPRESENTASI KRITIS KEMANUSIAAN DAN RESISTENSI - Fauzan, Muhamad Fatih (Multikultura, 2026)
This study examines the representation of the humanitarian crisis and popular resistance in the poetry of Sudanese demonstrators, drawing on the documentary film Sudan, Remember Us (2024) by Hind Meddeb. Using Norman Fairclough’s Critical Discourse Analysis (CDA), the study analyzes data that have been recontextualized through social media. The results show the use of dehumanizing lexicon (lāji'an, mumazzaqan) and hyperbolic metaphors to depict the suffering of the Sudanese people. The poetry employs intertextuality with the story of the Prophet Job to morally legitimize the victims, and is distributed through social media platforms. At the macro level, this poetry functions as a counter-discourse to deconstruct military hegemony and challenge international compassion fatigue. This phenomenon demonstrates digital poetry as an important space of resistance for oppressed groups to maintain human dignity.